Retrobulbar hemodynamic parameters in men and women with open angle glaucoma - Marjanović, Ivan; Marjanović, Marija; Gvozdenović, Ranko; Risović, Dušica (Vojnosanitetski pregled, 2014)
Background/Aim. Several factors may have influence on systemic circulation. Additionally, peripheral circulation also demonstrates sex differences, in young women presenting significantly lower finger blood flow in comparison to men of the same age, a finding that disappears in women after menopause. The aim of this study was to compare the retrobulbar hemodynamic parameters measured by means of color Doppler imaging in women and men with open-angle glaucoma and elevated intraocular pressure. Methods. A total of 52 eyes from 52 open-angle glaucoma (OAG) patients, with elevated intraocular pressure (IOP), were included in this cross-sectional study. Peak-systolic velocity (PSV), end-diastolic velocity (EDV), and Pourcelot resistivity index (RI) were assessed in the ophtalmic artery (OA), central retinal artery (CRA), and posterior cilliary arteries (PCA). IOP was measured both with Goldmann Applanation tonometer (GAT) and with the dynamic contour tonometer (DCT), three times respectively. Ocular pulse amplitude (OPA) appeared during the DCT measurement. Results. The retrobulbar hemodynamic parameters did not show any difference between men and post-menopausal women. Conclusion. The results of our study did not find any difference between sexes in patients with open-angle glaucoma and elevated intraocular pressure.